USING MULTI-CRITERIA ANALYSIS FOR THE STUDY OF HUMAN IMPACT ON AGRO-FORESTRY-PASTORAL ECOSYSTEM IN THE REGION OF KHENCHELA (ALGERIA) - A. Bouzekri; H. Benmessaoud (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
The objective of this work is to study and analyze the human impact on agro-forestry-pastoral ecosystem of Khenchela region through the application of multi-criteria analysis methods to integrate geographic information systems, our methodology is based on a weighted linear combination of information on four criteria chosen in our analysis representative in the vicinity of variables in relation to roads, urban areas, water resources and agricultural space, the results shows the effect of urbanization and socio-economic activity on the degradation of the physical environment and found that 32% of the total area are very sensitive to human impact.